Apoptotic cell capture by DCs induces unexpectedly robust autologous CD4+ T‐cell responses. Issue 8 (11th June 2014) - Valente, Michael; Baey, Camille; Louche, Pauline; Dutertre, Charles‐Antoine; Vimeux, Lene; Marañón, Concepción; Hosmalin, Anne; Feuillet, Vincent
<x xml:space="preserve">Abstract</x> Apoptotic cells represent an important source of self‐antigens and their engulfment by dendritic cells (DCs) is usually considered to be related to tolerance induction. We report here an unexpectedly high level of human CD4+ T‐cell proliferation induced by autologous DCs loaded with autologous apoptotic cells, due to the activation of more than 10% of naive CD4+ T cells. This proliferation is not due to an increase in the costimulatory capacity of DCs, but is dependent on apoptotic cell‐associated material processed through an endo‐lysosomal pathway and presented on DC MHC class II molecules. Autologous CD4+ T cells stimulated with apoptotic cell‐loaded DCs exhibit suppressive capacities. However, in the presence of bacterial lipopolysaccharide, apoptotic cell‐loaded DCs induce the generation of IL‐17‐producing cells. Thus, apoptotic cell engulfment by DCs may lead to increased autologous responses, initially generating CD4+ T cells with suppressive capacities able to differentiate into Th17 cells in the presence of a bacterial danger signal such as LPS.